APPLICATION OF THE ROLE PLAY METHOD IN IMPROVING THE LINGUISTIC INTELLIGENCE OF CHILDREN AGED 5-6 YEARS AT THE JULIANDI ISLAMIC SCHOOL BENTENG HILIR KINDERGARTEN - yanti, Hari; khadijah, khadijah (Universitas Al-Hikmah Indonesia, 2024)
Multiple intelligence is a theory of intelligence within children which can be a reference in developing the potential of early childhood. Linguistic intelligence is one branch of multiple intelligence. Linguistic intelligence is a child's verbal intelligence which includes writing, reading, listening and listening. From this statement, it is necessary Further research was conducted on children's linguistic intelligence through the role-playing method. This is research aims to improving the linguistic intelligence of early childhood by using the role-playing method at Juliandi Islamic School Benteng Hilir Kindergarten. This type of research uses classroom action research (PTK) which includes 4 components namely planning, implementation, observation and reflection carried out in 2 cycles. subjects of this is research children aged 5-6 years in group b of Kindergarten Juliandi Islamic School Benteng Hilir. The data collection technique in this research is observation and documentation. The instruments used in this research are student activity observation sheets and data collection is carried out by directly observing children's speaking skills and tests on children's speaking skills are carried out in the form of role playing. From this results of research conducting , shows that children's linguistic intelligence can increase through that applications of role-playing methods. in the pre-cycle it was 28.3%, in cycle 1 it was 43.7% and in cycle II it increased to 79.9%. This shows that the research results using the role-playing method can improving the linguistic intelligence of children 5-6 years at Juliandi Islamic School Benteng Hilir Kindergarten.